(untitled) (@limentech, Ciencia y Tecnología Alimentaria, 2016)
Chronic kidney disease is a global public health problem that is increasing daily. People with this condition must follow a low-potassium diet. To this end, dietary guidelines for chronic kidney disease recommend limiting the consumption of many fruits and using cooking methods that minimize the amount of potassium present in foods. Therefore, the objective of this study was to analyze the potassium reduction in bananas soaked for different times (0, 12, and 24 hours). The potassium content of duplicate samples was analyzed using flame atomic absorption spectrometry. The results showed significant reductions in potassium (12.36% between 0 and 12 hours of soaking, 35.01% between 12 and 24 hours, and 56.95% after 24 hours) and phosphorus (0.11%, 32.07%, and 32.15%, respectively) content at the different soaking times. The results showed that it is possible to reduce potassium and phosphorus levels with different soaking times, and the data obtained serve as a reference for professionals who treat these types of patients. Further research of this type is recommended, using different cooking techniques that provide alternative food intake for patients with chronic kidney disease.